Five new species and one new combination in Brazilian Myrtaceae - Sobral, Marcos; Costa, Idimá G.; Souza, Marcelo C.; Zorzanelli, João Paulo F. (Phytotaxa, 2017)
Eugenia asema, E. trichogyna, Myrcia altomontana, M. fria and M. macucana are described and illustrated, and the new combination Eugenia subglomerata, based on Myrtus subglomerata, is proposed. Eugenia asema, from the state of Rio de Janeiro, seems related to E. subavenia, but has glabrous shining blades and smaller flowers; E. trichogyna, also from Rio de Janeiro, is apparently close to E. pluriflora, but has wider blades and pilose flowers with unequal pairs of calyx lobes; Myrcia altomontana, from Espírito Santo, is related to M. neocambessedeana, but differs by its denser indumentum and shorter inflorescences; M. fria, also from Espírito Santo, is apparently related to Calyptranthes pauciflora but has glabrous flowers and larger inflorescences, and M. macucana, from the state of Minas Gerais, is apparently close to Calyptranthes anceps, from which it is distinguished by its markedly shorter inflorescences. Additionally, conservation status is assessed for the species described here.